Synthesis of Dispersed and Self-Assembled Metal Particles in Epoxy via Aqueous to Organic Phase Transfer Technique - Noorul Ain, Mohd Akib; Nor Hashila, Mohd Hirmizi; Wei, Leng Tan; Noor Hana Hanif, Abu Bakar; Mohamad, Abu Bakar; Jamil, Ismail; Cheng, Hoon Teoh; Chun, Hwa See (Avestia Publishing, 2015)
A convenient and effective method of dispersing gold (Au), silver (Ag) and copper (Cu) particles in epoxy is described. Particles were synthesized in aqueous phase and subsequently dispersed in toluene-epoxy with or without the presence of curing agent. Sodium borohydride and 2-propanol were used as reducing and phase transfer agents respectively. The surface plasmon resonance (SPR) at ~ 540-620 nm, ~ 525 nm and ~450 nm confirms the presence of Cu, Au and Ag nanoparticles in the composites. No chemical interaction occurred between the metal particles and the epoxy or cured epoxy. Increase in epoxy content caused the size of the particles to decrease for all metals. The average particle size for Au, Ag and Cu in 1% and 10% epoxy are 3.9 nm and 2.5 nm, 10.1 nm and 3.2 nm as well as 8.1 nm and 5.9 nm respectively. Similar decreasing trend was also observed upon addition of curing agent. In all cases, metal nanoparticles exhibit self-assembly with inter-particle spacing of <10 nm. The absence of any curing peak in the DSC thermograms suggests that the composites are well cured before any of the DSC analyses were performed. The Tg of the metal-cured epoxy is higher than neat epoxy, that is 71.3 °C, 69.8 °C and 62.0 °C for Cu, Au and Ag respectively.